WEIGHT, PHYSICAL PERFORMANCE, AND PHYSICAL ACTIVITY ASSOCIATIONS AMONG SEDENTARY COMMUNITY-BASED AGING ADULTS. (11th November 2018) - Venditti, E; Glynn, N; Albert, S; Boudreau, R; Rager, J; Kieffer, L; Danielson, M; Newman, A
Abstract: Older adults are living longer with obesity and chronic health conditions, which threaten mobility and functional independence. Lifestyle interventions to manage weight, activity and prevent disability are warranted. Further understanding of the baseline associations among BMI, physical performance, and objective physical activity measures in diverse community-recruited samples could help to clarify goals and expectations for such interventions. The Mobility and Vitality Lifestyle (MOVE UP) study examines the impact of a healthy aging/weight intervention delivered by Community Health Workers. Here we report on the 122 MOVE UP participants with SenseWear Armband data, worn ≥ 90% per day for ≥ 3 days, and associated demographic, weight, and physical performance measures at baseline. The sample was 87% female, 33% black/other race. Mean (SD) age was 67.9 (4.2), BMI 34.5 (4.7), and participants had 3.1 (1.5) chronic conditions. This sample spent 21.1 hours/day (2.0) in sedentary activities. Average steps/day were modest, 4455 (2747) as were gait speeds of 0.98 meters/second. Full regression models showed average steps/day were reduced by 233 (55) for each year older (P <.0001), by 152 (49) for each unit of increased BMI (P < .01), and increased by 462 (126) per each tenth of a meter/second faster gait speed (P < .001). Other models demonstrated a significant inverse relationship between chair-stand completion time and average declines in steps per day. Focusing on incremental weight loss, aerobic and strength training goals could enhance mobility in aging adults but this needs to be addressed in a context of significant sedentary behavior.